2022
DOI: 10.1097/md.0000000000029423
|View full text |Cite
|
Sign up to set email alerts
|

Vertical split fracture of the vertebral body following oblique lumbar interbody fusion

Abstract: Rationale: Oblique lumbar interbody fusion (OLIF) is an effective and safe surgical technique widely used for treating spondylolisthesis; however, its use is controversial because of several associated complications, including endplate injury. We report a rare vertebral body fracture following OLIF in a patient with poor bone quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Some studies have shown that depression remarkably affects the cognitive ability of many elderly patients with fracture complicated with cerebrovascular accident. [33][34][35] Foreign scholars have found that depression often experienced by elderly patients with fracture complicated with cerebrovascular accident will affect cognitive ability, and insecurity will coexist with depression. A high level of insecurity will also affect the ability of cognitive adjustment.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that depression remarkably affects the cognitive ability of many elderly patients with fracture complicated with cerebrovascular accident. [33][34][35] Foreign scholars have found that depression often experienced by elderly patients with fracture complicated with cerebrovascular accident will affect cognitive ability, and insecurity will coexist with depression. A high level of insecurity will also affect the ability of cognitive adjustment.…”
Section: Discussionmentioning
confidence: 99%